Search for a fermiophobic Higgs boson decaying into diphotons in pp[over] collisions at sqrt[s] = 1.96 TeV. - Aaltonen, T; Adelman, J; Akimoto, T; Alvarez González, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Apresyan, A; Arisawa, T; et al. (2009)
A search for a narrow diphoton mass resonance is presented based on data from 3.0 fb;{-1} of integrated luminosity from pp[over ] collisions at sqrt[s] = 1.96 TeV collected by the CDF experiment. No evidence of a resonance in the diphoton mass spectrum is observed, and upper limits are set on the cross section times branching fraction of the resonant state as a function of Higgs boson mass. The resulting limits exclude Higgs bosons with masses below 106 GeV/c;{2} at a 95% Bayesian credibility level for one fermiophobic benchmark model.